Effect of Adherence with Clinical Outcomes and Quality of Life Primary Hypertension Patients in Pharmacy - Hutauruk, Dumartina; Khairunnisa; Wiryanto (Talenta Publisher, 2020)
This study aimed to examine the effect of adherence to clinical outcomes and the quality of life of primary hypertension patients in pharmacy. The studywas conducted cross sectionally involved 60 patients at one of the pharmacies in Medan, Indonesia. Adherence was obtained in the form of adherence levels measured using the MMAS-8 questionnaire, clinical outcomes assessed by measuring a patient's blood pressure, and quality of life assessed using the EQ-5D-3L questionnaire. Then the data were analyzed using the Spearmen rho test. Patients who participated in the study consisted of 24 men and 36 women. Almost patient has low adherence with blood pressure mean of 156/ 90 mmHg. The patient's quality of life was 77.7%. Adherence has a significant relationship to clinical outcomes (p<0.05) with a strong correlation of r= -0.745. Adherence has a relationship to quality of life (p<0.05) with moderate correlation r= 0.554. This study concluded that adherence has a correlation with clinical outcomes and the quality of life of primary hypertension patients.